Molluscum contagiosum and associations with atopic eczema in children: a retrospective longitudinal study in primary care - Olsen, JR; Piguet, V; Gallacher, J; Francis, NA (Royal College of General Practitioners, 2015)
Background Molluscum contagiosum (MC) is a common skin condition in children. Consultation rates and current management in primary care, and how these have changed over time, are poorly described. An association between the presence of atopic eczema (AE) and MC has been shown, but the subsequent risk of developing MC in children with a diagnosis of AE is not known.